Riba, share-tenancy and agrarian reforms - Tahir, Sayyid (Pakistan Institute of Development Economics, 1996)
Land tenureship may take the form of self-cultivation, contractual workers, leasing and partnership. This paper focuses on the last one known as muzara`ah or share-tenancy. After clarifying what riba stands for, it reviews the misgiving about share-tenancy as a case of riba. It also argues at length in favour of share-tenancy as a legitimate mode of land tenure in Shari`ah. Finally, it also draws attention to some reforms to ameliorate the negative aspects of share-tenancy arrangements currently in vogue.